A Characterization of Flat-Plate Heat Exchangers for Thermal Load Management of Thermoelectric Generators - Hana, Yakoob (My University, 2015)
Thermoelectric generator (TEG) is a solid state technology based on the Seebeck effect that can generate electrical power from waste heat. For continuous electrical power generation heat exchangers are integrated into the “cold side” and the “hot side” of the TEG such that a temperature difference across the TEG can be established and maintained. This thesis will focus on characterizing two different flat-plate cold side heat exchanger prototypes specifically designed for dissipating the thermal loads from TEG modules. The majority of TEGs modules available have a flat geometry design and a square shape with typical dimension of 40 mm × 40 mm or 56 mm × 56 mm. To maximize the net electrical power generated by the TEGs the cold side heat exchanger is required to have uniform surface temperature distribution, and excellent heat transfer performance with minimum pressure drop. To achieve the previously mentioned requirements, two flat-plate heat exchanger prototypes having two distinct heat transfer techniques were investigated. Each heat exchanger is designed to accommodate an array of 14 TEG modules arranged in two parallel rows with 7 TEGs per row a typical arrangement for large waste energy harvesting applications. The first heat exchanger prototype utilized single-phase forced convection through 140 minichannels (1 mm × 1 mm × 90 mm long) as a heat transfer technique. The second prototype utilized 14 liquid jets, 3 mm in diameter and 40.3 mm apart, impinging on a flat surface located 5 mm above. Each impinging jets was positioned at the centre of the TEG cooling area. An experimental facility was constructed in order to test the minichannels heat exchanger and the impinging jets thermally and hydrodynamically. The heat transfer, pressure drop and temperature distribution results were compared to determine the most appropriate cold side heat exchanger prototype for the TEG POWER system. The TEG POWER system is a waste heat recovery system designed to recoup waste heat from the exhaust gases of commercial pizza ovens. The TEG POWER system is capable of harvesting waste thermal energy produced by an establishment and utilize it for electrical power generation and thermal storage purposes. Heat transfer results indicated that for a given mass flow rate the minichannels heat exchanger has better heat transfer performance compared to the impinging jets heat exchanger. The minichannels heat exchanger design had a thermal conductance of 238 W/C at 0.19 kg/s coolant flow rate compared to 111 W/C for the impinging jets heat exchanger. The total pressure drop and the minor losses for each heat exchanger prototype were measured experimentally. For the minichannels heat exchanger, the total pressure drop is 23.3 kPa at flow rate of 0.235 kg/s. Comparatively, the total pressure drop for the impinging jets heat exchanger was 27.4 kPa at the same flow rate. Fittings losses for the minichannels heat and impinging jets heat exchanger were found to be 50% and 80% respectively. The maximum total measured drop corresponded to pumping power requirements of 5.7 W and 6.8 W for the minichannels and impinging jets heat exchanger respectively. Local and average temperature distributions and their influence on the electrical power generated were studied for both heat exchanger prototypes. It was found that the minichannels heat exchanger offers more uniform surface temperature distribution per row of TEGs compared to the impinging jets heat exchanger. Therefore the minichannels heat exchanger is well suited for cooling two rows of TEGs simultaneously. Based on the thermal and hydrodynamics comparison results the minichannels heat exchanger prototype is recommended for implementation in the TEG POWER system.
Keywords: Flat-plate; Thermoelectric generator; Minichannel; Impinging jets; Heat exchangers; TEG